Using artificial odors to optimize attractiveness of host decoy traps to malaria vectors - Akoton, R.; Sawadogo, S.P.; Tossou, E.; Nikiema, A.S.; Tchigossou, G.; Sovegnon, P.M.; Djogbenou, L.; Zeukeng, F.; Hawkes, F.M.; Dabire, R.K.; Djouaka, R.; Gibson, G. (Oxford University Press, 2024)
Malaria vector surveillance tools often incorporate features of hosts that are attractive to blood-seeking females. The recently developed host decoy trap (HDT) combines visual, thermal, and olfactory stimuli associated with human hosts and has shown great efficacy in terms of collecting malaria vectors. Synthetic odors and yeast-produced carbon dioxide (CO2) could prove useful by mimicking the human odors currently used in HDTs and provide standardized and easy-to-use olfactory attractants. The objective of this study was to test the attractiveness of various olfactory attractant cues in HDTs to capture malaria vectors. We compared 4 different odor treatments in outdoor field settings in southern Benin and western Burkina Faso: the standard HDT using a human, HDT with yeast-produced CO2, HDT with an artificial odor blend, and HDT with yeast-produced CO2 plus artificial odor blend. In both experimental sites, the standard HDT that incorporated a real human produced the greatest catch of Anopheles gambiae s.l (Diptera: Culicidae). The alternatives tested were still effective at collecting target vector species, although the most effective included CO2, either alone (Benin) or in combination with synthetic odor (Burkina Faso). The trap using synthetic human odor alone caught the fewest An. gambiae s.l. compared to the other baited traps. Both Anopheles coluzzii and Anopheles gambiae were caught by each trap, with a predominance of An. coluzzii. Synthetic baits could, therefore, represent a more standardized and easier-to-deploy approach than using real human odor baits for a robust vector monitoring strategy.